The contribution of inflammasome components on macrophage response to surface nanotopography and chemistry - Christo, Susan (Sci Rep, 2016)
Implantable devices have become an established part of medical practice. However, often a negative inflammatory host response can impede the integration and functionality of the device. In this paper, we interrogate the role of surface nanotopography and chemistry on the potential molecular role of the inflammasome in controlling macrophage responses. To achieve this goal we engineered model substrata having precisely controlled nanotopography of predetermined height and tailored outermost surface chemistry. Bone marrow derived macrophages (BMDM) were harvested from genetically engineered mice deficient in the inflammasome components ASC, NLRP3 and AIM2. These cells were then cultured on these nanoengineered substrata and assessed for their capacity to attach and express pro-inflammatory cytokines. Our data provide evidence that the inflammasome components ASC, NLRP3 and AIM2 play a role in regulating macrophage adhesion and activation in response to surface nanotopography and chemistry. The findings of this paper are important for understanding the inflammatory consequences caused by biomaterials and pave the way to the rational design of future implantable devices having controlled and predictable inflammatory outcomes.